PROJECTIONS OF GLOBAL RETAIL E-COMMERCE SALES THROUGH TREND ANALYSIS AND FUTURE PREDICTIONS - Ridhani Ridhani; Mutiara Annisa; Risa Fitria Anisa; E Rusiadi; Suhendi Suhendi; E Lia Nazliana Nasution (JURNAL ILMIAH EDUNOMIKA, 2024)
E-commerce has had a positive impact on significant growth over the past decade, driven by rapid digital transformation and changes in consumer behavior. This study aims to project global retail e-commerce sales based on historical data from 2014 to 2023 obtained from Statista and eMarketer, estimating trends from 2024 to 2030 using the Autoregressive Integrated Moving Average (ARIMA) model. The methodology of this research employs a quantitative approach. The forecasting results show an increasing trend in e-commerce sales annually, with impressive projections for 2024 to 2030. The projection for 2024 is expected to reach $6,720.79 billion and is anticipated to gradually increase to $9,903.68 billion by 2030. This analysis provides essential insights for business strategy and policy planning in supporting e-commerce growth.